Genetic diversity assessment in Indian mustard (Brassica juncea L) for Alternaria blight tolerance using SSR markers - Praval Pratap; Ajay Kumar Thakur; PD Meena; HS Meena; Pankaj Sharma; Dhiraj Singh; Rita Majumdar (Journal of Oilseed Brassica, 2026)
Using SSR markers, genetic diversity in 20 Indian mustard [Brassica juncea (L.) Czern & Coss.] genotypes(14 advanced breeding lines, 4 tolerant germplasm accessions, 1 tolerant check, PAB 9511, and a susceptiblecheck Varuna) was evaluated for Alternaria blight tolerance. Genotypes DRMR 2805 and DRMR 2806found tolerant against Alternaria blight in the field conditions, gave the lowest AUDPC values of 10.0 and8.25, and average lesion size of 4.5 mm and 4.2 mm, respectively. Genetic diversity evaluated among 20Indian mustard genotypes using 25 Brassica species-derived-SSR markers, resulted into polymorphic ampliconsproducing a total of 88 alleles, ranging from 2 to 6 with an average number of 3.52 alleles/locus. The PICvalues ranged from 0.1073 (MB5) to 0.8173 (BRMS-017) with an average of 0.3503. The UPGMAdendrogram divided all 20 genotypes into 2 main clusters. Genotypes DRMR 2805 and DRMR 2806 sharedcommon cluster with PAB 9511, and were at par in their disease score indices to PAB 9511. The tolerantgenotypes DRMR 2805 and DRMR 2806 identified in the present study can be used for introgression ofAlternaria blight tolerance into the elite mustard cultivars in future breeding programmes